Gut Microbiota, Bacterial Translocation, and Stroke: Current Knowledge and Future Directions - Cristina Granados-Martinez; Nuria Alfageme-Lopez; Manuel Navarro-Oviedo; Carmen Nieto-Vaquero; Maria Isabel Cuartero; Blanca Diaz-Benito; Maria Angeles Moro; Ignacio Lizasoain; Macarena Hernandez-Jimenez; Jesus Miguel Pradillo (Biomedicines)
Stroke is one of the most devastating pathologies in terms of mortality, cause of dementia, major adult disability, and socioeconomic burden worldwide. Despite its severity, treatment options remain limited, with no pharmacological therapies available for hemorrhagic stroke (HS) and only fibrinolytic therapy or mechanical thrombectomy for ischemic stroke (IS). In the pathophysiology of stroke, after the acute phase, many patients develop systemic immunosuppression, which, combined with neurological dysfunction and hospital management, leads to the onset of stroke-associated infections (SAIs). These infections worsen prognosis and increase mortality. Recent evidence, particularly from experimental studies, has highlighted alterations in the microbiota–gut–brain axis (MGBA) following stroke, which ultimately disrupts the gut flora and increases intestinal permeability. These changes can result in bacterial translocation (BT) from the gut to sterile organs, further contributing to the development of SAIs. Given the novelty and significance of these processes, especially the role of BT in the development of SAIs, this review summarizes the latest advances in understanding these phenomena and discusses potential therapeutic strategies to mitigate them, ultimately reducing post-stroke complications and improving treatment outcomes.